Chronotope and Teaching Work in the Pandemic at the Federal Institute of Education, Science and Technology of Goiás (IFG) and at the State Department of Education of the Federal District (SEEDF) (Research, Society and Development, 2022)
In this article, we analyze the Bakhtinian concept of chronotope in teaching work organization during the COVID-19 pandemic, in two Brazilian educational systems: the Secretary of State for Education in Federal District - SEEDF, which offers Nursery, Elementary, High School, and Technological, Vocational Education and Training - TVET to all Federal District, and the Federal Institute of Education, Science and Technology of Goiás (IFG), which primarily offers Basic Education, especially High School Integrated to TVET, and the Higher education. Both institutions developed, throughout the pandemic, documents to direct and orient teachers and instructors’ work during the system called “remote class” or “emergency remote system” having on the one hand, specific and limited chronotopes of teachers’ practice and, on the other hand, very wide open and poorly directed chronotopes oriented. Those differences in the orientations, seen in official documents, generated ambiguity in the practices in the context of remote classrooms. The objective of this work was to develop a documental analysis of the guidance to teaching work during the pandemic in the years 2020 and 2021. As results, we observed the complexity through the task of teacher orientation, teaching times and spaces and educational objectives.